Quantifying the Seawater Sulfate Concentration in the Cambrian Ocean - Zhu, Guangyou; Li, Tingting; Huang, Tianzheng; Zhao, Kun; Tang, Wenbo; Wang, Ruimin; Lang, Xianguo; Shen, Bing (Frontiers in Earth Science, 2021)
Although the earliest animals might have evolved in certain “sweet spots” in the last 10 million years of Ediacaran (550–541 Ma), the Cambrian explosion requires sufficiently high levels of oxygen (O2) in the atmosphere and diverse habitable niches in the substantively oxygenated seafloor. However, previous studies indicate that the marine redox landscape was temporally oscillatory and spatially heterogeneous, suggesting the decoupling of atmospheric oxygenation and oceanic oxidation. The seawater sulfate concentration is controlled by both the atmospheric O2 level and the marine redox condition, with sulfide oxidation in continents as the major source, and sulfate reduction and pyrite burial as the major sink of seawater sulfate. It is thus important to quantify the sulfate concentration on the eve of the Cambrian explosion. In this study, we measured the pyrite contents and pyrite sulfur isotopes of black shale samples from the Yurtus Formation (Cambrian Series 2) in the Tarim Block, northwestern China. A numerical model is developed to calculate the seawater sulfate concentration using the pyrite content and pyrite sulfur isotope data. We first calibrate some key parameters based on observations from modern marine sediments. Then, the Monte Carlo simulation is applied to reduce the uncertainty raised by loosely confined parameters. Based on the geochemical data from both Tarim and Yangtze blocks, the modeling results indicate the seawater sulfate concentration of 8.9–14 mM, suggesting the seawater sulfate concentration was already 30–50% of the present level (28 mM). High seawater sulfate concentration might be attributed to the enhanced terrestrial sulfate input and widespread ocean oxygenation on the eve of the Cambrian explosion.